Comparative studies on the production of biodiesel from shea nut oil by acid catalyzed and supercritical transesterification processes - T Odisu; A Akemu; K.O. Obahiagbon; E.C. Anih (Journal of Applied Sciences and Environmental Management, 2019)
Shea nut oil has been confirmed as a feasible and sustainable biofuel source and may be used to improve the economics of biodiesel production. However, there is need to evaluate the best route for achieving optimum yield and best quality. Therefore, two processes were investigated in this study - acid catalyzed and supercritical transesterification processes. Shea nut seeds were collected, its oil mechanically extracted thereafter, and the physiochemical properties were analyzed. In the acid catalysed process, shea nut oil was transesterified into biodiesel using ethanol with sulphuric acid (H2SO4) as a catalyst. This gave a conversion of between 55wt% and 90wt% for temperatures between 20oC and 90oC. The optimum ratio of ethanol/oil was found to be 30:1 at 80oC for reaction time of 120 minutes. While for supercritical transesterification process (without acid), the conversion was between 55wt% and 82.5wt% at temperatures between 220oC and 300oC. However, the optimum condition here was 20:1 ethanol/oil molar ratio, at 240oC and 24 minutes reaction time. The biodiesel properties produced were evaluated and most of these conformed to Biodiesel Standard, ASTM D- 6751 and the international standard, EN-14214. Also, the properties of Biodiesel produced by supercritical process seem better compared to that from the acid catalyzed process in line with the ASTM D – 6751 and EN-14214 standards, thus a better option for diesel engines making supercritical transesterification a preferred option for biodiesel production from shea nut oil.